Investment Matters : The Role and Patterns of Investment in Southeast Europe - Handjiski, Borko (World Bank, 2012)
The purpose of this note is to provide policy insights to decision makers, academics, and researchers on the trends in investment in Southeast Europe (SEE). A comprehensive assessment of what determines investment is essential to identify, to the extent needed, policy actions that stimulate it. The report looks more in-depth into private investment trends in SEE, and explores some determinants of private investment, such as: the financing sources for investment, the contribution of Foreign Direct Investment (FDI), and the role of public investment. The selection has been made based on the relative importance and data availability for the SEE economies. Some key determinants of investment such as political stability and business environment have not been included because these are already well covered in the existing literature. Overall, the report aims to assess not only the quantity but also the quality of investment. It should be noted that while (investment in) human capital is equally, if not more, important for economic growth, its role and patterns in SEE are beyond the scope of this report.